Teaching Educational Materials on Natural Resources of Regions in Chemistry Lessons Through Mobile Software Applications - Nabatovna, Bekimbetova Gulnaz (Universitas Muhammadiyah Surakarta, 2025)
With the rapid development of science and technology across the world, modern and promising scientific fields are emerging. Alongside educating students about these promising fields and their significance, it is crucial to incorporate information in school chemistry lessons on local natural raw materials, their types, regional natural resources, raw materials derived from them, and their contribution to the national economy.Currently, Uzbekistan is implementing systematic reforms aimed at improving the quality and efficiency of the education system, forming modern knowledge and skills among students, ensuring closer cooperation and integration between educational institutions and the field of science, and maintaining continuity and consistency in education.In recent years, the current state of the national educational system has necessitated its modernization in line with contemporary requirements-cultivating knowledgeable, intellectually and physically healthy individuals; enhancing the status of educational institution leaders and teaching staff; and creating the necessary conditions for their effective professional activity.In chemistry lessons, explaining educational content through the integration of everyday natural phenomena and processes, as well as using materials related to the local natural resources, can enhance understanding. Integrating these materials with curriculum topics and using the latest scientific research effectively is facilitated by employing digital technologies, particularly mobile software applications.Mobile applications play a key role in the efficient and swift presentation of educational materials during lessons, using various media such as images, diagrams, audio and video materials, and virtual laboratory simulations.